Sex-specific Risk Factors for Cardiovascular Disease in Women - Płaczek, Alicja; Machaj, Dominik; Białas, Filip; Cyboran, Katarzyna; Siedlak, Agnieszka (Journal of Education, Health and Sport, 2022)
CVD is the leading cause of death for women worldwide. The symptoms of CVD in women may be less specific than in men, so women are less likely to be properly diagnosed and adequately treated. Women experience a proportional increase in cardiovascular risk on risk factors that are common to both genders. In addition, women have endocrine-related factors that increase their susceptibility to CVD. 1 in 3 women die from CVD, and 45% of women over the age of 20 have some form of CVD. [33] We must exploit gender differences to ensure optimal medical care. Detection of CVD risk factors and preventive measures in this regard are essential for proper cardiovascular care among women.